In vitro release of propolis from gelatin microparticles prepared by spray-drying technique - Bruschi, M. L. [UNESP]; Lopes, R. S. [UNESP]; Franco, S. L.; Gremião, Maria Palmira Daflon [UNESP] (My University, 2004)
The purpose of this study was to investigate the in vitro release of propolis from gelatin microparticles. Gelatin microparticles containing propolis extractive solution (PES) were prepared by spray-drying technique. Microparticles with a mean diameter of 2.50 μm and with regular morphology were obtained. The entrapment efficiency of propolis in the microparticles was over 39%. Spray-drying showed to be a feasible method for the preparation of gelatin microparticles containing propolis. Comparing to PES, the in vitro release of propolis from gelatin microparticles in aqueous medium was slower, considering markers 1 and 2. Thus, it was possible to transform a liquid propolis dosage form into a solid one, improving manipulation, packaging and storage and with modified release in aqueous medium, comparatively to the ethanolic extract of the drug.
Keywords: Gelatin; In vitro release; Microencapsulation; Microparticles; Propolis; Spray-drying; gelatin; nanoparticle; propolis; aqueous solution; drug release; feasibility study; in vitro study; morphology; spray drying; technique